Netralitas Aparatur Sipil Negara Pada Pemilukada 2024 di Kabupaten Lombok Tengah - Abdul Rahman; Lalu Zaenudin; Lalu Satria Utama (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
The neutrality of State Civil Apparatus (SCA) is a fundamental principle that must be upheld in the implementation of Regional Head Elections (Pemilukada). This study aims to analyze violations of the neutrality of State Civil Apparatus, particularly in the Social Service Office of Central Lombok Regency, during the 2024 Regional Head Elections. The design of this study is qualitative research. The results of the study indicate that the neutrality of the State Civil Apparatus in the 2024 Regional Head Elections in Central Lombok Regency shows a very strong political dynamic affiliated with the incumbent candidate pair.